Afro-Brazilians : Cultural Production in a Racial Democracy - Afolabi, Niyi (Book collections on Project MUSE., 2009)
Two faces of racial democracy -- Quilombhoje as a cultural collective -- Beyond the curtains : unveiling Afro-Brazilian women writers -- (Un)broken linkages -- The tropicalist legacy of Gilberto Gil -- Afro-Brazilian carnival -- Film and fragmentation -- Ancestrality and the dynamics of Afro-modernity -- The forerunners of Afro-modernity -- (Un)transgressed tradition -- Ancestrality, memory, and citizenship -- Quilombo without frontiers -- Ancestral motherhood of Leci Brandão.